Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content1. Availability of competencies among teachers of gifted, talented, and creative students in governmental schools in PalestineMrs. Wafa' Subhi Mustafa2. The Degree to Which Computer Teachers at The Secondary Stage Possess Blended Learning CompetenciesMrs. Sarah Zaid Al-Otebi, Dr. Ashwaq Abdellah Al-Sahim3. Challenges of Employing Interactive Simulations in Teaching Science Subjects to Intermediate  and Secondary Levels from the Viewpoint of Science Teachers in MadinahDr. Hanaa Eid Alharbi, Mrs. Basimah Saleem Alofi4. The degree of employing electronic management skills among public school principals  in The West Bank provinces from their PerspectivesMrs. Alaa Radi Nasser, Dr. Hussam Husni Al-Qasem5. Difficulties in providing support services for female students with intellectual disabilities  from the point of view of intellectual education teachers in Buraydah CityMrs. Salma Abdulrahman Al Bin Hamad6. Sexual features Among individuals with Autism Disorder and the way of Dealing with them from parents and care workersDr. Seham Reyad Alkhuffash7. Future Anxiety and Problem-Solving Skills as Predictors of Suicidal Ideation among Female University StudentsMrs. Raghad Saleh Al-Mufyid, Dr. Ahmed Ali Al-Homaidhi
Keywords: Journal of Educational and Psychological Sciences